DINAMIKA KEBIJAKAN PEMEKARAN WILAYAH DALAM PERSPEKTIF INOVASI KEBIJAKAN: ANTARA KESIAPAN DAERAH DAN PEMERATAAN PEMBANGUNAN - Iin Piani; Muslih Faozanudin (Jurnal Kebijakan Pemerintahan, 2025)
Regional expansion encounters obstacles, such as constrained economic capacity, administrative difficulties, and social disputes that frequently impede the attainment of these objectives.  Data indicates that numerous New Autonomous Regions (DOB) do not attain financial autonomy and fail to deliver adequate public services.  This essay seeks to evaluate the dynamics of regional expansion policies through the lens of policy innovation by assessing regional preparedness and equitable development.  The employed methodology is a literature review.  Regional expansion must be executed through a comprehensive method that encompasses meticulous planning, adequate budget allocation, and enhanced human resource capabilities.  Innovations in public policy, including participatory governance and community engagement, are essential techniques to address issues and enhance the beneficial effects of policies.  Consequently, regional growth programs necessitate rigorous assessment and oversight to guarantee their advantages for equitable development and community well-being. Keywords: regional expansion, public policy, New Autonomous Region, innovation policy, equitable development